Sistema para mejorar la productividad y confiabilidad del proceso de empaque para productos moldeados por inyección en Panduit de Costa Rica Ltda - Ramírez-Espinoza, William (Instituto Tecnológico de Costa Rica, 2016)
This document describes each one of the steps necessary to carry out the project "System to improve productivity and reliability of the packaging process by molded injection of Panduit of Costa Rica Ltda." Different phases are covered methodologically as: overview of the project, the design process with its own analysis, solution selection and implementation of a testing and process monitoring system. To understand the problem presented by Panduit, it will start by establishing certain generalities that will be found throughout the project, such as definitions and explanations of processes within the area where improvements are wanted. The project is to monitor production within the molding packaging line, with the help of global productivity standards such as OEE (overall equipment effectiveness) which is calculated from indicators of quality, efficiency, and productivity. Obtaining the OEE will justify, with actual productivity results, the decisions to make improvements on the plant Also, to improve the productivity and reliability of the packaging process, will be analized a proposal to implement a robot in one of the packaging lines.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica, Área Académica de Ingeniería en Mecatrónica, 2015.
Keywords: Base de datos; Producción; Monitoreo; Robots